Acceptance of postplacental intrauterine contraceptive device: recent increase in trend - K., Kanmani; G., Gokulakrishnan; P. R., Rani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: IUCD is a temporary method of contraception in use for many years. Our main objective is to find the acceptance of (postplacental intrauterine contraceptive device) PPIUCD in recent years. Methods: Retrospective Analysis was carried out to collect information regarding IUCD insertion in all women delivered at semi urban based medical college in Tamil Nadu from April 2014 to March 2016. Results: Total women delivered in our hospital were 20949 over a period of two years. Two year comparative study revealed significant increase in acceptance of PPIUCD insertion among primipara from 39.1% TO 68.9%. Acceptance of PPIUCD in primipara was 51.6% in first year (April 2014 to March 2015) to 87.8% in second year (April 2015 to March 2016).Most of the women were in the age group of 20 to 29 years (81.5%). Conclusions: The present study being retrospective analysis showed sudden increase in coverage rate of PPIUCD from 2014-2015 to 2015-2016. Though the patients were motivated in the same way throughout the period, training and motivation given to the staff nurses and duty doctors in the labour ward for PPIUCD insertion and daily review instead of weekly had brought the significant increase in the coverage. This clearly shows the role of service provider in the success of a national program though acceptor is always ready in most of the times.